Digital storytelling: How does it work for tertiary students’ speaking skill? - Mila Arizah (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2021)
While it is still rewarding nowadays to use storytelling in language classroom, it mostly used in kindergarten, secondary, adult, and higher education respectively. Studies of English by storytelling are uncommon in the higher education and undergraduate levels and the way to increase technology is preferred to be a part of the language classroom, particularly in teaching speaking.Teaching speaking has the function of reducing certain disincentives. The instructor needs to provide learning opportunities as much as possible.Then there is also a need for an engaging learning environment to stimulate the drive of the students to speak.Digital storytelling is a media-based story to help the learners find a better way to discover the target language's ability to communicate. Digital storytelling media is a combination of text, voice, narration, music, sound effects, pictures, and graphics to create a fictional or non-fictional interactive narrative. This study aimed at investigating whether or not digital storytelling effective to improve the students’ speaking skills. This experimental study was participated by 26third semester students of BaturajaUniversity,, majoring in English Education Study program.The study revealed that it was effective to use digital story telling in improving the third students’ speaking ability of Baturaja University. Keywords: speaking skill; digital storytelling